Towards Canada as Aesthetic State: François-Xavier Garneau’s Canadien Poetics - Findlay, Len (Studies in Canadian Literature, 2007)
Québec poet and historian François-Xavier Garneau's occasional poem "A Lord Durham" (1838) shows how poetry can tacitly draw on theories of the aesthetic state. Garneau's poem uses them to articulate the challenges facing Canadiens immediately before and after Lord Durham completed his influential Report on the Affairs of British North America (1839). Public poetry, when taken seriously, can help us understand how English capital and the English language were both welcomed and resisted by an emergent class of francophone artists and intellectuals. The social theories of Walter Benjamin, Mathew Arnold, Niklas Luhmann, and Jacques Rancière help explain how Garneau's poem engages poetical and aesthetic theory, poetic practice, and the writing of Québecois history in the mid-nineteenth century.